(untitled) (Texas Journal of Engineering and Technology, 2022)
In the article, the process of evaporation of fruit and vegetable juice in an evaporating apparatus, despite its relatively low productivity, can be attributed to continuous-acting apparatuses, which excludes the possibility of complete evaporation of juice, but at the same time its evaporation is necessary to the required density.